Perbedaan Keberadaan Jentik Aedes Aegypti antara Bak Mandi di Perdesaan dan Perkotaan di Kecamatan Wonogiri - Sidiq, Muhammad Nur (2016)
Background. As an effort of reducing the number of dengue sickness, a checking of larva is necessary. The checking of mosquito larva means to see the existence of Aedes aegypti larva which aims at knowing whether there are larva or not in the water container especially bath-tub. The reason is that bathup is one of potential places for the proliferation of Aedes aegypti mosquito. To know whether there are Aedes aegypti larva or not can be seen from the aspect of areas such as in rural area and urban area. From both areas, it can be seen the differences of characteristics in demography, such as population density and population mobility, the badness or the goodness of transportation infrastructure, and the pattern of mosquito distribution in residence area. Method. This research used the type of observational analitical research using a cross sectional approach. This research was conducted in the area of Wonogiri Sub-district in October-November 2015. The amount of sample was 100 respondents in Wonogiri Sub-district area distributed in 15 urban and rural villages. Variables of this research consisted of: rural and urban areas and the existence of Aedes aegypti larva. Data was obtained through a visual method, which was a direct observation. The statistical test used was Chi square. Results. The existence of Aedes aegypti larva in urban area was more than the one in rural area (42%: 14% dengan p= < 0.002; p=<0.05), thus Ho was rejected and H1 was accepted that meant that there was difference of the existence of Aedes aegypti larva between the bath-tub in rural area and the bath-tub in urban area in Wonogiri Sub-district. Conclusion. The conclusion was that there was difference of existence of Aedes aegypti larva between bath-tub in rural area and bath-tub in urban area in Wonogiri Subdistrict.